Morphine Enhances HIV Infection of Neonatal Macrophages - Li, Yuan (2003)
Perinatal transmission of HIV accounts for almost all new HIV infections in children. There is an increased risk of perinatal transmission of HIV with maternal illicit substance abuse. Little is known about neonatal immune system alteration and subsequent susceptibility to HIV infection after morphine exposure. We investigated the effects of morphine on HIV infection of neonatal monocyte-derived macrophages (MDM). Morphine significantly enhanced HIV infection of neonatal MDM. Morphine-induced HIV replication in neonatal MDM was completely suppressed by naltrexone, the opioid receptor antagonist. Morphine significantly up-regulated CCR5 receptor expression and inhibited the endogenous production of macrophage inflammatory protein-1β in neonatal MDM. Thus, morphine, most likely through alteration of β-chemokines and CCR5 receptor expression, enhances the susceptibility of neonatal MDM to HIV infection, and may have a cofactor role in perinatal HIV transmission and infection.